2021
DOI: 10.3390/genes12111811
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Expression Changes between Genes Controlling 5-HT Synthesis and Genes Crh and Trh in the Midbrain Raphe Nuclei of Chronically Aggressive and Defeated Male Mice

Abstract: Midbrain raphe nuclei (MRNs) contain a large number of serotonergic neurons associated with the regulation of numerous types of psychoemotional states and physiological processes. The aim of this work was to study alterations of the MRN transcriptome in mice with prolonged positive or negative fighting experience and to identify key gene networks associated with the regulation of serotonergic system functioning. Numerous genes underwent alterations of transcription in the MRNs of male mice that either manifest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…In this work and in our previous studies [ 25 , 26 , 45 , 46 , 47 , 48 , 59 ], we focus on DEGs encoding proteins that are related to reward-associated neurotransmitters in the brain: opioid-, catecholamine-, GABA-, and glutamatergic systems, which partake in the regulation of aggression in the VTA, STR, and NAcc (which are considered the main regions implicated in aggression stimulation) and in the MRNs and PFC, which as a rule, perform inhibitory functions toward aggressive behavior [ 6 ].…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In this work and in our previous studies [ 25 , 26 , 45 , 46 , 47 , 48 , 59 ], we focus on DEGs encoding proteins that are related to reward-associated neurotransmitters in the brain: opioid-, catecholamine-, GABA-, and glutamatergic systems, which partake in the regulation of aggression in the VTA, STR, and NAcc (which are considered the main regions implicated in aggression stimulation) and in the MRNs and PFC, which as a rule, perform inhibitory functions toward aggressive behavior [ 6 ].…”
Section: Discussionsupporting
confidence: 55%
“…Analysis of the RNA-Seq database of MRNs [ 48 ] revealed the largest number of DEGs of interest in this main region processes ( Figure 5 A, Supplementary Table S1 ). Opioidergic gene Oprd1 was upregulated ( p = 0.009) and CAergic genes were downregulated: Th ( p < 0.001; q = 0.035), Ddc ( p < 0.001; q = 0.005), Dbh ( p < 0.001; q = 0.005), Sncg ( p < 0.046), Drd2 ( p = 0.03), and Slc18a2 ( p = 0.04).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well known that the main neurotransmitter systems-catecholaminergic (CAergic), serotonergic, opioidergic, GABAergic, and glutamatergic-are involved in the mechanisms of reward, drug abuse, addiction, and aggression [e.g., 6,12,[28][29][30][31][32][33]. Our neurotranscriptomic and cellular studies on mice experienced in aggression have revealed alterations of the expression of numerous genes specific for brain regions depending on their main functions in the regulation of aggression mechanisms [16,[18][19][20][21][22][23][24]34]. For example, in the VTA, which is the main brain region involved in reward mechanisms, an increase has been revealed in the expression of CAergic (Th, Ddc, Slc6a2, and Slc6a3), glutamatergic (Slc17a7 and Slc17a8), and opioidergic (Oprk1) genes (and others) encoding relevant proteins [16].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that MRNs contain a large number of serotonergic neurons associated with the regulation of numerous types of psycho-emotional states and physiological processes. The article by Redina and colleagues focuses on an analysis of the co-expression of DEGs and Tph2-encoding tryptophan hydroxylase 2, the rate-limiting enzyme of the serotonin synthesis pathway [ 4 ]. The results showed that Tph2 expression correlated with the expression of many DEGs, associated with behavior, learning, memory, and synaptic signaling.…”
mentioning
confidence: 99%